Acute Myocardial Infarction in a Patient with Two-Vessel Occlusion and a Large Lambl's Excrescence. (22nd November 2016) - Pizzuti, Alfredo; Parisi, Francesco; Mosso, Luciano; Cali' Quaglia, Francesca; Tomasello, Antonino
Abstract : A 59-year-old man underwent an echocardiography study after myocardial infarction and it showed a thin, mobile mass attached to the aortic valve. A diagnosis of Lambl's excrescence (LE) was suspected. Coronary occlusion as a consequence of embolism of LE's material could not be excluded and the patient underwent surgical excision. Histology confirmed the diagnosis; however a differential diagnosis with papillary fibroelastoma could not be established because both of these structures are histologically indistinguishable. A brief survey of the literature is presented. Evidence-based recommendations for treatment have not been established yet.